THE CURRENT STATE OF THE EUROPEAN DARK BEE SUBSPECIES Apis mellifera mellifera L. IN THE NORTH RANGE OF THE RUSSIAN FEDERATION - Chugreev, M.K.; Baimukanov, D.A.; Blokhin, G.I.; Malovichko, L.V.; Zubaliy, A.M.; Skvortsova, E.G.; Doshanov, D.A.; Tkacheva, I.S.; Kruglov, S.A. (Scientific Journal of Pedagogy and Economics, 2020)
The research to determine the factors with a negative impact on the resource status of honey bees in the Russian Federation has been done. Based on the research results, a simple and affordable rapid test for determining the origin of bees was proposed, based on the study of a complex of morphological and biological characteristics of working bees, such as proboscis length, cubital index, discoid displacement, the shape of the rear border of the wax plate of sternite 5, body color, the character of the honey seal, behavior of bees during the examination of the nest and phototaxis. The test is suitable for detecting bee crossbreeding during their mass selection since the listed morphological and biological traits are the most contrasting and indicative among others. The indicated morphological and biological characteristics of bees from the Yaroslavl, Vologda, Kostroma regions, Perm Territory were studied. In the Susaninsky district of the Kostroma region, the bee colonies were identified that correspond to the European dark bees Apis mellifera mellifera L. according to the studied traits. From them, breeding material was taken and evaluated for further breeding and the creation of a nursery reproducer. In conclusion, a landmark is given, a promising direction of work is indicated for the conservation and restoration of the resources of the European dark bees in the current conditions of mass unsystematic crossbreeding in the north of their historical range.